WaveCoder: Widespread And Versatile Enhanced Instruction Tuning with Refined Data Generation - Yu, Zhaojian; Zhang, Xin; Shang, Ning; Huang, Yangyu; Xu, Can; Zhao, Yishujie; Hu, Wenxiang; Yin, Qiufeng (2024 Meeting of the Association for Computational Linguistics, 2024)
Recent work demonstrates that, after instruction tuning, Code Large Language Models (Code LLMs) can obtain impressive capabilities to address a wide range of code-related tasks. However, current instruction tuning methods for Code LLMs mainly focus on the traditional code generation task, resulting in poor performance in complex multi-task scenarios. In this paper, we concentrate on multiple code-related tasks and present WaveCoder, a series of Code LLMs trained with Widespread And Versatile Enhanced instruction data. To enable the models to tackle complex coderelated tasks, we propose a method to stably generate diverse, high-quality instruction data from open source code dataset in multitask scenarios and obtain CodeSeaXDataset, a dataset comprising 19,915 instruction instances across 4 code-related tasks, which is aimed at improving the generalization ability of Code LLM. Our experiments demonstrate that WaveCoder models significantly outperform other open-source models in terms of the generalization ability across different code-related tasks.